Empirical seismic vulnerability analysis for masonry buildings based on school buildings survey in Iran - Azizi-Bondarabadi, Hamed (2016)
School facilities in Iran, in particular masonry schools, have shown poor performance during past earthquakes and can be identified as one of the parts of the country’s infrastructure that is most vulnerable to earthquakes. Hence, in this paper a method to perform index-based damage assessment for brick masonry schools located in the province of Yazd, the central region of Iran, using a comprehensive database of school buildings, is proposed. The database was obtained from the field survey forms applied for each observed school to collect the features of and damage to the structure. The results of a vulnerability index method developed in Iran are employed as input data to obtain empirical fragility curves for the school inventory. The Macroseismic model and GNDT II level method are two empirical methods combined in this procedure. Finally, the procedure is verified using damage survey data obtained after recent earthquakes (1990 Manjil–Rudbar earthquake and 2003 Bam earthquake) that occurred in Iran.